Cultural inspirations towards Malaysian animation character design - Faryna Mohd Khalis,; Normah Mustaffa, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Culture is part of human development which evolves with civilization from ancient times to today’s digital era. Animation contributes to the cultural industry through signs and symbols and is captured from people’s different lifestyle and various grounds including religion, belief systems, politics, tradition, language, tools, costumes, buildings and arts. Wayang Kulit or ‘Shadow Play’ was once a famed traditional culture in the 1960s for entertainment purposes in Malaysia which fundamentally led to the continuation of the 2D and 3D animation studies. Nevertheless, students these days seem lack the sense of local identity as shown in their final animation project, as if the culture sentiment is getting faded. Since culture is also emerging with an identity where both fundamentals are strongly connected, this research aims to identify the influence of culture towards artwork, produced by art and design students who study animation. Content analysis was used to analyze the complete final artwork from selected university in Sarawak which offers this subject as a requirement. Besides a good storyline, animation must have a strong character design with a good personality, appropriate costumes and accessories. Results found that there are cultural influences where the character’s costume design is similar to the Sarawak traditional clothing. Thus, it proves that Malaysian culture is still sturdily inspiring students in creating their artwork.